Effect mechanism of acidic SiO2 nanofluids on coal wettability and gas desorption - Xianfeng LIU; Chuang LI; Baisheng NIE; Xueqiu HE; Xueqi JIA; Chengyi HE; Han HAN (Meitan xuebao)
The addition of nanofluid can change the chemical structure of coal and then moisten the coal and affect the process of gas desorption. In order to explore the effect of acidic SiO2 nanofluid on the moistening mechanism of coal powder and the law of gas desorption, the experiment is configured with modified coal samples of acidic SiO2 nanofluid with different concentrations and pH values. Contact Angle measurement experiment is used to explore the effect of acidic SiO2 nanofluid on the wettability of coal from a macroscopic perspective. The law of methane desorption of modified coal samples under the action of infiltrating solution with different pH values and different SiO2 nanofluid concentrations was studied. Fourier infrared spectroscopy and scanning electron microscopy were used to analyze the wetting mechanism of acidic SiO2 nanofluid on coal powder and the promoting mechanism of coal gas desorption. The results show that the content of SiO2 nanofluid and suitable weak acid environment can promote the enhancement effect of coal body. When the saturated solution is in a weak acid environment with SiO2 nanofluid content of 2.0% and pH of 3, the measured contact Angle is 25.2°,which is 74.5° lower than that of raw coal. The gas desorption capacity increased from 6.9607 mL/g to 13.2794 mL/g. With the enhancement of weak acid acidic environment and the increase of SiO2 nanofluid concentration in the experiment, the contact Angle gradually decreases, the coal gradually changes from hydrophobic to hydrophilic, the wetting effect is enhanced, and the promoting effect of gas desorption is enhanced. As the main groups affecting the wettability of coal, the total absorption peak area is negatively correlated with the coal-water contact Angle, and positively correlated with the gas desorption amount and gas desorption rate of coal. The surface morphology of different modified coal samples also changed. Reasonable selection of acidic SiO2 nanofluid to infiltrate the coal body can enhance the wettability of the coal, achieve efficient coal dust removal, promote the process of gas desorption, and strengthen the effect of gas extraction.